Improving the strategy for using rechargeable battery energy storage systems to enhance the economic efficiency of photovoltaic power plants in the electricity market - Kulyk, Volodymyr; Zatkhei, Maksym; Teptia, Vira; Hrytsiuk, Yurii; Vishnevskyi, Sviatoslav; Hrytsiuk, Iryna (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates operational process involving rechargeable battery energy storage systems (ESSs) in a combination with photovoltaic power plants (PVPPs) in the competitive electricity market. The task addressed is to improve the functioning efficiency of electric power systems with deep PVPP penetration. This work analyzes scenarios and strategy optimization when using ESSs to increase the economic efficiency of PVPPs operating in a single complex. The research results established those factors that affect the technical and economic indicators of ESS application and helped define a combined management strategy. Practical ESS management scenarios with different mechanisms for forming an economic effect were studied, in particular, the day-ahead market arbitrage scenario (DAM) and the PVPP balancing scenario. The latter, in addition to minimizing the costs of settling imbalances, provides for the sale of excess stored energy during hours of maximum price. The use of an ensemble of machine learning methods (RandomForest + XGBoost + LightGBM) has made it possible to achieve high accuracy in forecasting PVPP generation. Energy indicators were optimized for each scenario of ESS control system; financial results were assessed based on the MILP and MPC methods. That made it possible to quantitatively compare the effectiveness of the arbitrage and balancing strategies and justify the choice of ESS operation mode depending on the volatility of the DAM prices, the level of forecast uncertainty of generation, and the current rules for regulating imbalances in the electricity market. The results were verified on the example of a real 9.5 MW PVPP, supplemented by ESS with an energy capacity of 2 MWh, which made it possible to take into account the financial responsibility of the producer for imbalances and the impact of price asymmetry on the end result